FEATURES OF MICROELEMENT STRUCTURE OF BODIES AND FABRICS OF THE CASPIAN SEAL - L. Y. Nozdrina; V. F. Zaitsev; E. I. Melyakina (Юг России: экология, развитие, 2014)
Caspian seal - this is the only marine mammal in the Caspian Sea, a unique endemic species, which is listed in the Red Book of World Conservation Union as a species under threat. Over-exploitation of the Caspian seal population fisheries, the impact of invasive species, disease, pollution and other factors lead to a substantial reduction in population size. Since the beginning of the twentieth century and the present strength of the Caspian seal population has declined almost to 2-2,5 times.